After dark: the nocturnal urban landscape and lightscape of ancient cities - Gonlin, Nancy, editor; Strong, Meghan E., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2022)
After Dark explores the experience of nighttime within ancient urban settings. Contributors present evidence related to how ancient people manipulated and confronted darkness and night in urban landscapes, advancing our knowledge of the archaeology of cities, the archaeology of darkness and night, and lychnology (the study of ancient lighting devices).--Provided by publisher.
City Nights: Archaeology of Night, Darkness, and Luminosity in Ancient Urban Environments -- Looking for Light in Ancient Egyptian Urban Rituals-- Danger in the Mesopotamian Night: Mitigating Peril in the Heartland of Cities -- Illuminating the Mysteries of the Great Gods at Samothrace, Greece -- Living Landscapes of Night in Tiwanaku, Bolivia -- Lunar Power in Ancient Maya Cities -- Every Day Hath a Night: Nightlife and Religion in the Wari Empire of Peru -- Cahokia after Dark: Affect, Water, and the Moon -- Notes on the Chacoan Nightscape: Astronomy, Fireboxes, and Gambling -- The Aztec New Fire Ceremony and the Illumination of the Night -- Nocturnal Urban Landscapes: From the First Cities to the Present.
Keywords: Cities and towns, Ancient; Municipal lighting -- History; City and town life -- History; Lighting -- Social aspects; Night -- Social aspects; Sociology, Urban